New Insights on Childhood Lupus Nephritis - Marchi-Silva R; De Aquino BM; Londe AC; Mazzola TN; Julio PR; Wampler Muskardin T; Appenzeller S (International Journal of Nephrology and Renovascular Disease)
Rodrigo Marchi-Silva,1,2 Bruna Martins De Aquino,1,2 Ana Carolina Londe,1,2 Ta&iacgr;s Nitsch Mazzola,3 Paulo Rogério Julio,4 Theresa Wampler Muskardin,5,6 Simone Appenzeller2,7 1Medical Pathophysiology Graduate Program, School of Medical Science, Universidade Estadual de Campinas, Campinas, Brazil; 2Autoimmunity Lab, School of Medical Science, Universidade Estadual de Campinas, Campinas, Brazil; 3Center for Molecular Biology and Genetic Engineering (CBMEG), Universidade Estadual de Campinas, Campinas, Brazil; 4Child and Adolescent Graduate Program, School of Medical Science, Universidade Estadual de Campinas, Campinas, Brazil; 5Hospital of Special Surgery, Department of Medicine, New York, NY, USA; 6Weill Cornell Medicine, Department of Medicine and Department of Pediatrics, New York, NY, USA; 7Department of Orthopedics, Rheumatology and Traumatology, School of Medical Science, Universidade Estadual de Campinas, Campinas, BrazilCorrespondence: Simone Appenzeller, Faculdade de Ciências Médicas (FCM)/Hospital de Clínicas (HC) – UNICAMP, Vital Brasil Street, 251, Campinas, SP, 13083-888, Brazil, Tel +55 11 98887-8693, Email appenzel@unicamp.brAbstract: Approximately one in five patients with systemic lupus erythematosus (SLE) has disease-onset during childhood (cSLE). Lupus nephritis is more common in cSLE than adult-onset SLE and is associated with significant and increased morbidity and mortality. In this article, we review lupus nephritis in cSLE, including pathogenesis, diagnosis, biomarkers, and management through PUBMED search between July and December 2024. Diagnosis of lupus nephritis is made in 93% of cSLE patients during the first 2 years of disease. The majority of patients have active disease in other organs, and nephrotic range proteinuria and hypertension is frequently observed at diagnosis. Class III and IV are observed in over 50% of renal biopsies and progression to end-stage renal disease varies across cohorts. Major progress made in recent years includes adjustment of the proportion of fibrous crescents when scoring nephritis in cSLE to better discriminate kidney disease outcomes, and development of non-invasive biomarkers to identify renal disease activity and damage. It is anticipated that accurate non-invasive biomarkers will foster multicenter studies and help identify new treatment approaches to improve outcomes in cSLE nephritis.Keywords: lupus nephritis, childhood-onset SLE, treatment